2001
DOI: 10.1677/joe.0.1680131
|View full text |Cite
|
Sign up to set email alerts
|

Systemic prostaglandin E2 increases cancellous bone formation and mass in aging rats and stimulates their bone marrow osteogenic capacity in vivo and in vitro

Abstract: Prostaglandin E 2 (PGE 2 ) has been shown to exert a bone anabolic effect in young and adult rats. In this study we tested whether it possesses a similar effect on bone formation and bone mass in aging rats. Fifteen-month-old rats were injected daily with either PGE 2 at 5 mg/kg or vehicle for 14 days. PGE 2 treatment stimulated the rate of cancellous bone formation (a 5·5-fold increase in bone formation rate), measured by the incorporation of calcein into bone-forming surfaces at the tibial proximal metaphysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…Authors: The authors believe this is a very exciting area of study with many possible factors at work. An interesting molecule to focus on could be PGE2, which has been shown to have anabolic effects for cancellous bone formation in aged rats (Keila et al, 2001). The same study found that when PGE2 was applied to bone marrow MSCs in vitro there was an increase in the number of mineral nodules.…”
Section: Discussion With Reviewersmentioning
confidence: 97%
See 1 more Smart Citation
“…Authors: The authors believe this is a very exciting area of study with many possible factors at work. An interesting molecule to focus on could be PGE2, which has been shown to have anabolic effects for cancellous bone formation in aged rats (Keila et al, 2001). The same study found that when PGE2 was applied to bone marrow MSCs in vitro there was an increase in the number of mineral nodules.…”
Section: Discussion With Reviewersmentioning
confidence: 97%
“…Cbfa1 (Runx2) and osteocalcin are expressed in higher quantities by osteocytes than osteoblasts (Mikuni-Takagaki et al, 1995;Ducy et al, 1997) and might be responsible for the quicker www.ecmjournal.org E Birmingham et al Osteogenesis of MSCs in a simplifi ed bone niche osteogenic response in MSCs exposed to osteocyte factors. Certain pro-osteogenic signalling molecules, such as nitric oxide (NO) and prostaglandin E2 (PGE2), are released in large amounts from mechanically stimulated osteocytes in vitro (Klein-Nulend et al, 1995a;Klein-Nulend et al, 1995b;Keila et al, 2001), but are also expressed in static conditions (McAllister et al, 2000;Cheng et al, 2001). These signals could provide the stimuli for MSC osteogenic differentiation in vivo.…”
Section: Osteogenesis Of Mscs In a Simplifi Ed Bone Nichementioning
confidence: 99%
“…The finding that the COX-2 metabolite PGE 2 can reverse the decrease in osteoblastogenesis observed in COX-2 -/-marrow cell culture is not surprising given the effect of PGE 2 on bone formation both in vitro and in vivo (6,7,42,47,48). However, the finding that BMP-2 complements the deficiency in COX-2 and enhances bone nodule formation to a degree similar to that observed in wild-type cultures is particularly interesting and suggest that BMP signaling events may be downstream of COX-2 activity and PGE 2 effects.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, systemic or local injection of PGE 2 stimulates bone formation in vivo and appears to induce osteoblastogenesis from bone marrow precursors (7,47). Ex vivo cultures of bone marrow stromal cells from rats injected with PGE 2 for 2 weeks yield four times more mineralized bone nodules compared with cultures from vehicleinjected rats (47 Schematic model representing the potential mechanism of COX-2 regulation of mesenchymal cell differentiation in bone repair. In the proposed model, COX-2 is induced in the early phase of the bone reparative process and produces increased amounts of PGE 2 in the local milieu.…”
Section: Figurementioning
confidence: 99%
“…It is also possible that calcium concentration determines, indirectly, the cellular response to mechanical stimulation (osteogenesis or bone resorption) because this ion is responsible for 83% of PGE 2 synthesis. Additionally, the anabolic effects of PGE 2 are mediated by EP2 prostaglandin receptor and, mainly, by EP4 prostaglandin receptor, both located at the nuclear membrane (Cherian et al, 2005;Fortier et al, 2001;Genetos et al, 2005;Ke et al, 2003;Keila et al, 2001;KleinNulend et al, 1997;Li et al, 2005;Machwate et al, 2001;Mullender et al, 2004;Nomura & Takano-Yamamoto, 2000;Reich et al, 1997;Watanuki et al, 2002;Xu et al, 2007).…”
Section: Prostaglandinsmentioning
confidence: 99%